Escherichia coli O78 isolated from septicemic lambs shows high pathogenicity in a zebrafish model. (January 2018) - Kjelstrup, Cecilie; Barber, Amelia; Norton, J.; Mulvey, Matthew; L'Abée-Lund, Trine
Abstract The pathogenicity ofEscherichia coli O78 strain K46, originally isolated from an outbreak of septicemia in neonatal lambs, was investigated in zebrafish embryo and murine models of infection. Its biofilm potential, cellulose production, and the expression of type 1 pili and curli fimbriae were measured by in vitro assays. The strain was highly pathogenic in the zebrafish embryo model of infection, where it killed all embryos within 24 h post inoculation (hpi) at doses as low as 1000 colony forming units. Zebrafish embryos inoculated with similar doses of commensalE. coli strains showed no signs of disease, and cleared the bacteria within 24 h.E. coli K46 colonized the murine gut at the same level as the uropathogenicE. coli (UPEC) reference strain CFT073 in CBA/J mice after oral inoculation, but infected the murine bladder significantly less than CFT073 after transurethral inoculation. Type 1 pili were clearly expressed byE. coli K46, while curli fimbriae and cellulose production were weakly expressed. The ability to produce biofilm varied in different growth media, but overallE. coli K46 was a poorer biofilm producer compared to the reference strainE. coli UTI89. In conclusion, the zebrafish lethality model provides further evidence thatE. coli K46 is highly pathogenic and might be useful in future studies to identify bacterial virulence factors.